2015
DOI: 10.1038/aps.2014.137
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the pentose phosphate pathway alters phase I metabolism of testosterone and dextromethorphan in HepG2 cells

Abstract: Aim:The pentose phosphate pathway (PPP) is involved in the activity of glucose-6-phosphate dehydrogenase (G6PD) and generation of NADPH, which plays a key role in drug metabolism. The aim of this study was to investigate the effects of modulation of the PPP on drug metabolism capacity in vitro. Methods: A pair of hepatic cell lines, ie the cancerous HepG2 cells and normal L02 cells, was used. The expression of CYP450 enzymes, p53 and G6PD in the cells were analyzed. The metabolism of testosterone (TEST, 10 μmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The medium was refreshed 2 or 3 times a week and, up to approximately 80% to 90% confluence, cells were detached from the petri dish with a 0.25% trypsin‐ethylenediaminetetraacetic acid solution (Beyotime) for subculture at a 1:4 split ratio. As cell lines can be changed over time in culture, cells within 20 passages from the originally purchased vial from the American Type Culture Collection were used to control for genomic drift due to instability . To deplete endogenous steroids in the gene expression studies, the media were changed to phenol red‐free medium containing 10% charcoal/dextran‐FBS (Gemini Bio Products, Sacramento, CA) for 48 hours before experimentation …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The medium was refreshed 2 or 3 times a week and, up to approximately 80% to 90% confluence, cells were detached from the petri dish with a 0.25% trypsin‐ethylenediaminetetraacetic acid solution (Beyotime) for subculture at a 1:4 split ratio. As cell lines can be changed over time in culture, cells within 20 passages from the originally purchased vial from the American Type Culture Collection were used to control for genomic drift due to instability . To deplete endogenous steroids in the gene expression studies, the media were changed to phenol red‐free medium containing 10% charcoal/dextran‐FBS (Gemini Bio Products, Sacramento, CA) for 48 hours before experimentation …”
Section: Methodsmentioning
confidence: 99%
“…As cell lines can be changed over time in culture, cells within 20 passages from the originally purchased vial from the American Type Culture Collection were used to control for genomic drift due to instability. 14 To deplete endogenous steroids in the gene expression studies, the media were changed to phenol red-free medium containing 10% charcoal/dextran-FBS (Gemini Bio Products, Sacramento, CA) for 48 hours before experimentation. 15 For all experimental treatments, cells in the logarithmic growth phase were plated in 96-or 6-well plates with a density of 5 × 10 3 and 3 × 10 5 cell per well, respectively, according to different experimental purposes.…”
Section: Cell Culture and Steroid Treatmentmentioning
confidence: 99%
“…The inhibition of meiosis resumption by 6-AN following sperm penetration into zona-free oocytes was also associated with the PPP [26] . Furthermore, 6-AN directly modulates the PPP signal pathway to trigger metabolic disorders, especially the drug metabolism, in HepG2 and other cancer cells [27] , indicating that 6-AN generated metabolic disorders of liver cancer. However, there are no reports of 6-AN on HBV replication [28] .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study found that spontaneous PPP impairment in tumours could stimulate chk2/p53/p65 expression (Wang et al, ). In addition, the modulation of p53 and PPP could alter the metabolism of CYP3A substrates in HepG2 cells and LO2 cells (Xiao et al, ). Here, we found that the chk2/p53/p65 pathway was stimulated in the liver along with the impaired PPP (Figure a–d).…”
Section: Discussionmentioning
confidence: 99%